KafÄâ€™ah in Kiai á¹¢Äliá¸¥ Darat's Perspective - Irfan, Agus; Amri, Muhammad Saeful (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2020)
According to Kiai á¹¢Äliá¸¥ Darat, kafÄâ€™ah means equal or similarity between the prospective bridegroom and bride in their perfect nature and lack. There are five categories of kafÄâ€™ah, 1) survivors of marital defects, 2) independence, 3) noble people, 4) fair and â€˜iffah in religion, 5) good limbs and work. For him, property is not included in the category of kafÄâ€™ah because it cannot be measured and can be lost at any time. Using library research with the primary source of the book Majmuâ€™Ät al-SharÄ«'ah al-KÄfiyah li al-â€˜Awam by Kiai á¹¢Äliá¸¥ Darat, the concept of kafÄâ€™ah will be elaborated. The collected data were analyzed using interpretive descriptive methods. This study concludes that treasure is not a priority in the kafÄâ€™ah category because it is not a gift but a trial. Treasure is not something noble, because it is not the legacy of noble people such as prophets, apostles, and previous salih people but the inheritance of despicable people like Qarun, Hamman, and Pharaoh. An ahlul â€˜ilmi who married his daughter to ahlul arto, because of his wealth, he changed from ahlul â€˜ilmi to ahlul jahli.